Integrated Woodencraft Cluster : Program Akselerasi Usaha Kecil dan Menengah (UKM) Go International sebagai Upaya Pemberdayaan UKM Potensial Yogyakarta - Ismianti Ismianti; Yun Prihantina Mulyani; Rasyid Halimi; Oktiyanto Ade Saputro (OPSI, 2019)
Small and Medium Enterprises (SMEs) have a very important role in the development of the Indonesian economy. Special Region of Yogyakarta (DIY) is one of the provinces that has many SMEs. The SMEs has the potential to penetrate the international market, one of which is a wooden handicraft SMEs. Woodencraft can be used as a cluster because it fulfills three factors that enable it to compete in the international market, namely the factor of global market needs, the factor of superior products, and potential SME product factors. However, woodencraft SMEs still face obstacles in product penetration abroad, namely obstacles from internal SMEs, the government, and international markets. The solution offered to help woodencraft SMEs to go international a program called Integrated Woodencraft Cluster, which is a cluster of woodencraft SMEs that integrates supply chain management (SCM) based distribution systems with four main lines (suppliers, production, sales, and information), internet-based information systems, and Just In Time (JIT) principle. The program involves local government, civil service, wood handicraft SMEs, suppliers of raw materials, and academics. The advantages of Integrated Woodencraft Clusters compared to conventional clusters include having a clear vision for exporting production, a structured managerial system, having an export agency, supplying raw materials, clear lines of information, and being able to facilitate all SME woodencraft, both on a small scale and intermediate.